Determinants of Children’s Emotional and Behavioral Problems among Preschool Children in Kelantan: From Parent’s Perspective - Nurul Najwa Husna Rosdi; Siti Fatimah Ab Ghaffar; Suchi Hassan; Nur Dalila Mat Yusoff; Hamidin Awang (Symbiohealth, 2026)
Preschool children with emotional and behavioral problems (EBP) are at risk of having mental health problems in adulthood. The goal of this study is to determine the prevalence of EBP and identify the predictors of EBP among preschool children in Kelantan. A cross-sectional study was conducted among 180 parents of children who are attending preschool. A set of questionnaires consisted of Strength and Difficulties Questionnaire (SDQ), Parenting Emotional Style Questionnaire (PESQ), Asian Family Characteristic Scale (AFCS), and Service Quality Questionnaire (SERVQUAL) to measure i) EBP, ii) parental emotional styles, iii) family values, iv) teacher's empathy, and learning environment and items, respectively. The overall prevalence of EBP was 16.1%. The prevalence of peer problems, hyperactivity problems, conduct problems, and emotional problems was 51.7%, 12.8%, 9.4%, and 6.1%, respectively. Based on Multiple Logistic Regression, parental occupational status (p = 0.046), family value (p = 0.021), and emotion dismissing parental styles (p = 0.002) were significant predictors of EBP, while there was no significant relationship between parental marital status, parental educational level, teacher's empathy, learning environment and items and emotion coaching parental styles. Therefore, early intervention is urgently needed to minimize EBP and prevent these problems in Kelantan.